Sistem Pendukung Keputusan Dalam Pemilihan Karyawan Terbaik Di Pt. Smartlink Global Media Dengan Metode Weight Product - Ramadhani, Wiwied Wahyu, Nurgiyatna, ST., MSc., PhD (2017)
Best and qualified employees will make a company be increased in operation and can develop rapidly. However, the constraints on the PT. Smartlink Global Media which is a private enterprise telecommunications provider in Solo, still not optimal in the implementation of the election of the best employees. It is therefore necessary human resource management in an enterprise with the selection of the best employees to boost morale in improving operations, dedication and performance of the company so that it becomes better, namely to create a decision support system in the selection of the best employees by using the method of weight product. Product weight method is a method using multiplication decision to link the value of the criteria, which is where the value for each criterion should be raised to a first weighing the relevant criteria (Monica et al, 2015). This decision support system is a tool that can provide solutions and help administrators in the electoral process is computerized tebaik employees to be more effective and efficient. From calculations using the method of weight product can know the best employees of the alternatives that exist in a company. The research proves that the application is able to assist in the selection process admin selecting the best employees with methods of product weight, as well as providing the best employee information effectively and efficiently with a percentage of 91.5%